Pengaruh Non-Performing Financing (NPF) Pada Bank Umum Syariah Di Indonesia Terhadap Pembiayaan Musyarakah Periode Tahun 2015-2019 - Sutiana, Sutiana (JYRS: Journal of Youth Research and Studies, 2021)
This study aims to determine the effect of Non Performing Financing (NPF) on Islamic Commercial Banks in Indonesia on Musyarakah Financing for the 2015-2019 Period. This research uses quantitative descriptive research, which is a type of research that produces findings that can be achieved or obtained using statistical procedures or other methods. The results of this study indicate that there is a significant effect based on the results of the T test. The results of the study show that the significance value of NPF Nett is 0.000 <0.05. This value can be defined that 76.9% of the musyarakah financing variables can be explained by the NPF Nett Individual method, the remaining 23.1% is explained by other variables outside of this study. And for future researchers, it is expected to add other variables that affect musyarakah financing that are not in this study such as ROA, ROE, BOPO, CAR, TPF, so that the results further strengthen musyarakah financing obtained from Islamic Commercial Banks